A Comparison of Ultra Sound Therapy and Micro Wave Diathermy on Patients with Adhesive Capsulitis of Shoulder Joint (Journal of Armed Forces Medical College, Bangladesh, 2019)
Introduction: Adhesive capsulitis is one of the most common causes of pain and disability of the shoulder joint. Most patients are managed conservatively in a primary care setting with the expectation of a good outcome. There are many alternative forms of treatment for this condition. Several interventions are also used in combination for its management but most of it remained unclear. Ultra Sound Therapy (UST) is commonly employed as a first line agent for the management of adhesive capsulitis. But whether the UST (Ultra Sound Therapy) and MWD (Micro Wave Diathermy) therapy would produce a significant difference in out come was not yet settled.Objective: To compare the efficacy of ultra sound therapy (UST) and micro wave diathermy (MWD) for the management of patients with adhesive capsulitis of shoulder joint.Materials and Methods: This observational study was carried out in the Department of Physical Medicine at Combined Military hospital, Dhaka from 01 May 2015 to 30 November 2015. A total of eighty patients were enrolled in this study and they were divided into two equal groups. One group received counseling plus UST (Ultra Sound Therapy) (1MHz @ 1.0 Watt/cm2 area for 10 minutes for two weeks) with physical exercise. Another group received counseling, MWD (Micro Wave Diathermy) and physical exercise for same period. Each group received the above mentioned modalities on the basis of five days a week for 06 weeks.Results: The result was observed by applying VAS (Visual analog scale) pain scale and SPADI (Shoulder Pain And Disability Index) pain score. The highest significant improvement (P